Bank Clearings Outside New York City, 1875-1914 - Frickey, Edwin (The Review of Economics and Statistics, 1925)
T HE object of this study was to obtain for the United States, for as long a period as possible prior to the outbreak of the World War, a continuous monthly index of business activity as indicated by the fluctuations of bank clearings. In the construction of this index two steps were involved: first, monthly aggregate clearings were secured for a representative group of cities; and second, these monthly aggregates were corrected for long-time trend and seasonal variation, in order that the fluctuations significant of cyclical changes in business activity might be clearly revealed. The results of this study are presented graphically in the two charts appearing as an insert placed opposite this page. Chart i shows monthly aggregate clearings for a group of 7 selected cities, I875-I9I4, together with lines of trend. Chart 2 compares the monthly adjusted relatives of the series of aggregate clearings, corrected for secular trend and seasonal variation, with adjusted relatives for pig-iron production, another series held to be indicative of business activity.'